O trabalho situado como resposta à complexidade institucional: um estudo da interseção entre a contabilidade gerencial e a mudança organizacional - Oliveira, Fabiano Siqueira de (2021)
The aim of this study is to understand the change and different uses of management accounting practices in face of institutional complexity by presenting a mini ethnographic case study in a family organization acquired by a business conglomerate that implemented changes to the management accounting practices used, emerging from an interaction complex of institutional pressures and situational and historical factors. The study analyzes this context of changes at the macro level that affect internal processes and results at the micro level, connecting a theoretical puzzle analyzed under the light of Institutional Theory, more specifically that of institutional logics, combined with the perspective of logics situated in the study of organizations, which outlines how 'situated logics' emerge that shape the use of management accounting practices, relating them to the basic assumptions taken for granted by different groups of actors. This study addresses a gap in the literature related to Institutional Theory, as it addresses the heterogeneity of practices in a more comprehensive and justified way of different uses. The way in which the diversity of practices is seen in organizations, lacking guidance and alignment, may be less a matter of minimizing tensions, a situation that inhibits the questioning of knowledge and information previously considered certain. The perspective developed in this study opens paths for promising research on the challenges that organizations face as they change, implicated in important questions on how organizations manage change as a constitution and capacity building mechanism for appropriate measures in everyday situations in organizations.